Korelasi Feritin dengan Sitokin Proinflamasi pada Pasien Talasemia Beta Di Kota Samarinda Kalimantan Timur - Muhammad Fahmi Aminuddin; Anton Budhi Darmawan; Lantip Rujito (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2022)
Introduction: Ferritin is a routine parameter used in the evaluation of iron overload in thalassemia patients. Excess iron causes the formation of ROS, resulting in an oxidative reaction that triggers inflammation. This study aims to determine the correlation of ferritin levels with proinflammatory cytokines in beta thalassemia. Methods: A cross-sectional analytical study was conducted on 33 beta thalassemia patients who received routine blood transfusions at I.A. Moeis Samarinda. Spearman rank correlation test was used to determine the correlation between ferritin and TNF-α and IL-6. Results: The results of this study showed that there was no relationship between ferritin and TNF- (p=0.580) and IL-6 (p=0.924). Meanwhile, there was a significant relationship between TNF- and IL-6 (p less than 0.0001) which had a strong positive correlation (r=0.621). Conclusion: This study showed that there was no correlation between ferritin levels with TNF-α and IL-6. Meanwhile, proinflammatory cytokines showed a correlation between TNF-α and IL-6 in thalassemia patients in Samarinda City.